Relationship between Dishonest Academic Behaviour and Students’ Attitudes towards School Offenses - Tovarovic, Jelena; Stevanović, Nikola (Psihološka istraživanja, 2023)
The goal of this study is to determine if there is a correlation between academic dishonesty and students’ attitudes toward school offenses. The research included 347 respondents from primary (seventh and eighth grades) and secondary (second and third grades) schools in Republic of Serbia. A Measurement of Dishonest Behaviour (MDB) was used to assess several types of dishonest behaviour: Plagiarism, Deception, Cheating, Sabotage, Bribery, and Aiding Others. The School Offenses Scale (SOS), which includes subscales for Copying, Running Away from Classes, Whispering, Falsifying School Documents, Rationalising Violence against Teachers and Professors, Bribery and Corruption, Nepotism, and General Attitude toward School Offenses, was used to evaluate the prevalence of immorality in attitudes toward school offenses. According to the findings, there is a significant positive relationship between dishonest behaviour and students’ attitudes regarding school offenses. The total score of students’ attitudes has the highest relationship with the subscale of dishonest behaviour connected to Deception, while the total score of dishonest behaviour has the highest correlation with several subscales of immoral attitudes: Running Away from Classes, General Attitude, Nepotism, Falsification, and Bribery and Corruption. The findings of canonical correlation analysis were discussed in this paper, which focused on the relationship between sets of behavioural scales and attitudinal scales. Furthermore, relationship between immoral attitudes and dishonest behaviour were explained through theory of cognitive dissonance, while possible ways of predicting dishonest behaviours and methods of reducing cheating and other types of dishonest behaviours are presented in the conclusion.